Students’ Voice on Their English Teacher’s Teaching Techniques: A Case Study at A Private Indonesian Junior High School - Bambang Widi Pratolo; Ani Susanti; Indriani Indriani (English Language Teaching Educational Journal, 2018)
This study is aimed to know the students’perception toward the English teacher’s teaching techniques. This study was conducted in grade eight of two EFL classes of a junior high school in Indonesia. The instruments to collect the data was a Likert-scale questionnaire with five options of strongly agree to strongly disagree, while to analyze the data the researcher used descriptive statistics by finding means, standard deviation and frequency. An in-depth interview was also conducted to nine out of 60 students to scrutinize the students’ voice on their English teachers’ performance. The result of the analysis showed that the teacher in this study performed all the three techniques, controlled, semi-controlled and free technique. The finding also showed that the most frequently used technique was controlled technique, followed by a semi-controlled and free technique. Meanwhile, most of the students have positive perception toward their English teacher’s teaching techniques.